RAFFLESIA HASSELTII SURINGAR (RAFFLESIACEAE): A NEW RECORD TO KALIMANTAN, INDONESIA - Rismita Sari; Miftahul Huda; Ratna Susandarini; Inggit Puji Astuti (BRIN Publishing (Penerbit BRIN), 2019)
SARI, R., HUDA, M., SUSANDARINI, R. & ASTUTI, I. P. 2019. Rafflesia hasseltii Suringar (Rafflesiaceae): A new record to Kalimantan, Indonesia. Reinwardtia 18(2): 65–70. –– Rafflesia hasseltii Suringar flower has been observed for the first time in Sambas District, West Kalimantan by the Flora Fauna Research Team during the Khatulistiwa Expedition organized by Special Forces Command of Indonesian Army in 2012. This finding is the first record of Rafflesia hasseltii in Kalimantan following the previous record in Sarawak. The flower has 5–6 perigone lobes. This paper presents the detail characteristic of the flowers.